Corporate Blogging and Job Performance: Effects of Work-related and Nonwork-related Participation - Lu, Benjiang; Guo, Xunhua; Luo, Nianlong; Chen, Guoqing (Journal of Management Information Systems, 2015)
Corporate blogs are expected to facilitate communication, knowledge sharing, and collaborative innovation within organizations. However, empirical evidence has yet to be found illustrating whether and how such applications have affected job performance. Drawing upon social network theory, we postulate a conceptual model suggesting that employees’ online social relationships accumulated through work- and nonwork-related blog participation will engender different effects on job performance. The model is empirically tested using digital trace and archival data collected from two in-practice systems of a large telecommunications company. The results reveal that, in the work-related blog network, the structural and cognitive dimensions of social relationships positively affect job performance, whereas the relational dimension shows a negative influence. Meanwhile, participation in nonwork-related blog network benefits job performance for employees with a high level of performance in the previous time period, but is detrimental for other employees. The findings uncover the influencing mechanism of corporate blogging on job performance and offer practical advice for managers to better exploit the value of intraorganizational social media.